Antimicrobial agent use in small animals what are the prescribing practices, use of PK‐PD principles, and extralabel use in the United States?. Issue 2 (23rd October 2020) - Papich, Mark G.
Abstract: In this review, the availability and deficiencies of current antimicrobial agents for companion animals in the United States are described. Although several active agents are FDA‐approved for small animals, there are many unmet needs. These needs are greatest for cats, for the treatment of antibiotic drug‐resistant infections, and to treat new or emerging pathogens that were not considered on older labels. The older agents approved before 1997 are often outdated, unavailable, or have inaccurate labeling. Subsequently, veterinarians treat dogs and cats with many unapproved antimicrobial agents that are licensed for human use. Although these drugs may be effective, there are also concerns that this use can produce drug‐resistant bacteria that may be a public health risk. Although this concern is real, there is also evidence that any antimicrobial use in small animals can produce resistant fecal bacteria and stewardship principles should aim at reducing any unnecessary antibiotic use. This could be accomplished by avoiding some of the older, ineffective, or outdated agents described in this paper. There is a need for incentives to approve new agents that will be more appropriate for treating infections in companion animals without increasing the risk of drug‐resistant bacteria that could potentially be transferred to humans and the environment and create a public health risk.